Ca3 (PO4) 2 crystal enhanced zwitter-ion hydrogel film as well as preparation method and application thereof
By grafting the zwitterionic hydrogel on the surface of the PVDF membrane and introducing Ca3(PO4)2 crystals, the problem of poor mechanical properties of the hydrogel membrane is solved, and the film is high mechanical stability and excellent pollution resistance are achieved, which significantly improves the oil-water separation efficiency and circulation performance.
Patent Information
- Application Number
- CN202411988016.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-31
AI Technical Summary
In the prior art, the mechanical properties of the hydrogel film are poor and prone to deformation and collapse during pressure-driven oil/water separation, resulting in a decrease in oil repellency and anti-fouling function.
Zwitterionic hydrogel was grafted on the surface of the PVDF membrane by polyphenol-metal dual autocatalysis method, and Ca3(PO4)2 crystals were introduced through mineralization technology to enhance the mechanical properties and contamination resistance of the membrane.
The prepared Ca3(PO4)2 crystal enhanced zwitterionic hydrogel film has an ultra-hydrophilic surface, excellent anti-pollution and high mechanical stability. It can operate stably for a long time, significantly improving oil-water separation efficiency and circulation performance.
Smart Images

Figure CN119775620A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a Ca3(PO4)2 crystal-enhanced zwitterionic hydrogel film and a preparation method and application thereof, belonging to the technical field of environmental functional material preparation. Background Art
[0002] Water is the source of life and the most precious resource on earth. With the progress of industrialization and urbanization, the treatment of oily wastewater has become a challenge. Oily wastewater mostly exists in the form of oil-in-water (O / W) emulsions. These emulsified oils are difficult to treat and will seriously damage the ecological environment and affect people's lives. Therefore, there is an urgent need for efficient oil-water separation technology to treat oily wastewater, purify water resources, and realize water recycling.
[0003] Membrane separation technology has attracted much attention due to its high efficiency, but hydrophobic membranes are easily contaminated. In recent years, researchers have developed TA-APTES coatings based on tannic acid (TA) and 3-aminopropyltriethoxysilane (APTES), which have the advantages of simple preparation, low cost, and wide application range, but have problems with poor stability and cycle performance.
[0004] At the same time, the hydration of membrane materials is crucial to their oil pollution resistance. The surface of membrane materials with strong hydration will form a hydration layer in water. This hydration layer can effectively prevent oil and other pollutants from directly contacting and adhering to the membrane surface, thereby reducing the pollution of oil to the separation membrane. At present, hydrogel materials and zwitterionic polymers are used to construct anti-pollution separation membranes due to their strong hydration ability. Hydrogel materials are a kind of polymer material with a three-dimensional network structure formed by cross-linking hydrophilic compounds rich in hydrogen bonding groups such as -COOH, -OH, and -NH2 through chemical and physical effects. It has super hydration and has been reported to have anti-pollution properties against a variety of oils. Zwitterionic polymers use the equal amount of positive and negative charge functional groups carried by each structural unit to combine with numerous water molecules through charge, and form a strong and stable hydration layer on the membrane surface through electrostatic interaction, thereby strengthening the "pollution resistance" mechanism on the membrane surface. Therefore, a dual autocatalytic system of polyphenols and metals was used on the surface of PVDF membrane modified with TA-APTES coating to initiate the polymerization of sulfobetaine-type amphiphilic ionic monomers, and a PVDF porous membrane (PSBMA@TA-APTES@PVDF gel membrane) grafted with sulfobetaine-type amphiphilic ionic nanohydrogel was prepared, which provides an effective means to solve the membrane fouling problem. However, due to the low Young's modulus and generally poor mechanical properties of hydrogels, their utility in practical applications is severely limited. Especially in the process of pressure-driven oil / water separation, hydrogels are easily deformed and collapsed under flow shear, resulting in a decrease in the oil repellency and antifouling function of the hydrogel-modified membrane.
[0005] Unlike most polymers, some inorganic materials are naturally endowed with excellent mechanical strength, chemical stability and hydrophilicity, which are conducive to the formation of a stable membrane hydrophilic structure. Combining the advantages of small pore size of polymer membranes and stable oil repellency of rigid inorganic materials, polymer / inorganic hybrid membranes with excellent hydrophilicity can achieve efficient separation of oil-water emulsions. Therefore, mineralization technology can be used to construct polymer / inorganic nanoparticle hybrid membranes. During the mineralization process, inorganic materials nucleate and grow at the molecular level and in restricted positions, which is conducive to the uniform dispersion of inorganic particles on the polymer membrane and greatly improves the hydrophilicity of the membrane. Therefore, mineralization of the prepared PSBMA@TA-APTES@PVDF hydrogel membrane can successfully solve the problems of low mechanical strength of zwitterionic hydrogel membranes and reduced anti-fouling performance in the oil-water separation process.
[0006] At present, there are few research reports in this area. The present invention combines multiple technologies, using micro-nanosphere coating, polyphenol-metal dual autocatalytic polymer technology and mineralization technology to prepare a new type of Ca3(PO4)2 crystal-enhanced zwitterionic hydrogel membrane, which is not only simple to operate and has a short modification reaction time, but also has a super-hydrophilic surface and excellent anti-pollution properties, and can operate stably for a long time. Summary of the invention
[0007] In view of the shortcomings of the prior art, the purpose of the present invention is to overcome the technical defects of the prior art. The present invention uses polyphenol modification and takes it as a secondary reaction platform. The polyphenol-metal dual autocatalytic method is used to induce the polymerization of sulfobetaine-type amphiphilic ion monomers on the PVDF membrane to prepare a PSBMA@TA-APTES@PVDF hydrogel membrane, and based on this, it is mineralized with Ca3(PO4)2 crystals to solve the problems of traditional separation membrane pollution, low flux and poor mechanical properties, so that the prepared new membrane can separate a variety of oil-water emulsions, greatly improve the separation efficiency and greatly improve the circulation performance.
[0008] A method for preparing a Ca3(PO4)2 crystal-enhanced zwitterionic hydrogel film comprises the following steps:
[0009] (1) Pretreatment of PVDF base membrane: Wetting with a certain amount of ethanol.
[0010] (2) Preparation of TA-APTES@PVDF membrane:
[0011] TA (about 40-60 mg) was dissolved in deionized water (about 20-30 mL), and then APTES with a volume of about 500-1000 μL was added, and the pretreated PVDF base membrane was placed in it. The reaction was shaken in a water bath at room temperature for about 30 min to 1 h to obtain a modified membrane with a rough surface modified by a micro-nanosphere coating.
[0012] (3) Preparation of PSBMA@TA-APTES@PVDF membrane:
[0013] Dissolve 0.058 g FeCl3·6H2O, about 0.005-0.025 g ammonium persulfate, about 0.01-0.02 g N,N-methylenebisacrylamide and about 0.1-0.5 g methacrylic acid sulfobetaine in 5-10 mL deionized water, place the membrane obtained in step (2) into the solution, and react in a water bath at room temperature for about 1-3 hours to obtain a zwitterionic hydrogel membrane.
[0014] (4) Preparation of Ca3(PO4)2 / PSBMA@TA-APTES@PVDF membrane:
[0015] Dissolve about 50-200 mg of anhydrous CaCl2 in 20 mL of deionized water, and soak the membrane obtained in step (3) therein for about 10-30 min; then soak it in water for 5-10 min; finally, transfer the membrane to a prepared KH2PO4 solution of about 60 mg / 20 mL to 80 mg / 20 mL and soak it for about 10-30 min to obtain a Ca3(PO4)2 crystal-enhanced zwitterionic hydrogel membrane.
[0016] The above-mentioned Ca3(PO4)2 crystal-enhanced zwitterionic hydrogel membrane was applied to oil-water separation experiments:
[0017] The volume ratio of water to oil in the oil-water emulsion used in this experiment was 99:1, and 20 mg of ionic surfactant was added and stirred for 12 hours to form a stable emulsion. Then, the oil-water separation experiment was performed using a suction filtration device. The concentration before emulsion separation was C0, and the concentration after emulsion separation was C p , calculate the separation efficiency R.
[0018]
[0019] Figure 6 The separation substances involved, cyclohexane, dichloroethane, toluene, hexane and petroleum ether, refer to the statistical data of separation of emulsions with a volume ratio of these substances to water of 1:99.
[0020] The beneficial effects of the present invention are:
[0021] (1) The present invention uses PVDF as the base film, which has low material price, good mechanical properties, is environmentally friendly, and has good recycling performance.
[0022] (2) Through the polyphenol-metal dual autocatalytic method, a layer of zwitterionic hydrogel is grafted on the surface of the PVDF membrane simply and efficiently without heating or ultraviolet light.
[0023] (3) Through mineralization technology, it is used to construct inorganic crystal-enhanced zwitterionic hydrogel membranes to prepare oil-water separation membranes with anti-pollution, good mechanical properties, and long-term stable circulation. This inorganic crystal-enhanced zwitterionic hydrogel membrane has the advantages of strong hydration performance and high mechanical stability, and has a high separation efficiency for water-in-oil emulsions, showing obvious anti-pollution performance and good cyclic stability.
[0024] (4) The preparation method of the present invention is simple, easy to operate, has low energy consumption, is easy to handle, and has no secondary pollution. It conforms to the concept of green chemistry and has good application prospects in the field of oil-water separation. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a scanning electron micrograph of the hydrophobic PVDF base membrane.
[0026] Figure 2 This is the scanning electron microscope image of Ca3(PO4)2 / PSBMA@TA-APTES@PVDF membrane.
[0027] Figure 3 This is a cross-sectional scanning electron microscope image of the Ca3(PO4)2 / PSBMA@TA-APTES@PVDF membrane.
[0028] Figure 4 The middle is the water contact angle of Ca3(PO4)2 / PSBMA@TA-APTES@PVDF membrane in air.
[0029] Figure 5 The figure in the middle is the underwater oil contact angle of Ca3(PO4)2 / PSBMA@TA-APTES@PVDF membrane.
[0030] Figure 6 The retention rate and oil-water flux of Ca3(PO4)2 / PSBMA@TA-APTES@PVDF membrane for cyclohexane, ethylene dichloride, toluene, n-hexane and petroleum ether.
[0031] Figure 7 Change of pure water flux (W) of Ca3(PO4)2 / PSBMA@TA-APTES@PVDF membrane in the cycle test.
[0032] Figure 8 The flux (O) change of Ca3(PO4)2 / PSBMA@TA-APTES@PVDF membrane in oil and water during the cycle test. DETAILED DESCRIPTION
[0033] The embodiments of the present invention are described in detail below:
[0034] This embodiment is implemented on the premise of the technical solution of the present invention, and provides a detailed operation process and specific reaction conditions, but the protection scope of the present invention is not limited to the following embodiments.
[0035] Example 1
[0036] Step 1: Pretreatment of PVDF base membrane: Moisten with a certain amount of ethanol, the amount of ethanol used should be enough to cover the PVDF base membrane.
[0037] Step 2: Preparation of TA-APTES@PVDF membrane:
[0038] TA (tannic acid) (50 mg) was dissolved in 25 mL of deionized water, and then 700 μL of APTES (3-aminopropyltriethoxysilane) was added, and the pretreated PVDF-based membrane (polyvinylidene fluoride membrane) was placed in a water bath for 40 minutes at room temperature to obtain a modified membrane with a rough surface modified by a micro-nanosphere coating. The room temperature is preferably 15° C. to 25° C.
[0039] Step 3: Preparation of PSBMA@TA-APTES@PVDF membrane:
[0040] 0.058 g FeCl3·6H2O, 0.01 g ammonium persulfate, 0.012 g N,N-methylenebisacrylamide and 0.1 g methacrylate sulfobetaine were dissolved in 6 mL deionized water, the membrane obtained in step (2) was placed in the solution, and the reaction was carried out under shaking in a water bath at room temperature for 2 h to obtain a zwitterionic hydrogel membrane.
[0041] Step 4: Preparation of Ca3(PO4)2 / PSBMA@TA-APTES@PVDF membrane:
[0042] Dissolve 50 mg of anhydrous CaCl2 in 20 mL of deionized water, and soak the membrane obtained in step 3 for 30 minutes; then soak it in water for 10 minutes; finally, transfer the membrane to the prepared 69.6 mg / 20 mL KH2PO4 solution and soak it for 30 minutes to obtain a Ca3(PO4)2 crystal-enhanced zwitterionic hydrogel membrane.
[0043] Figure 1 It can be seen that the surface of the hydrophobic PVDF base membrane is relatively smooth and the pore size is sparse.
[0044] Figure 2 It can be seen that the Ca3(PO4)2 / PSBMA@TA-APTES@PVDF membrane has inorganic nanoparticles, indicating that the mineralization of the membrane is successful.
[0045] Figure 3It can be seen that inorganic nanoparticles are successfully embedded in the pores of the Ca3(PO4)2 / PSBMA@TA-APTES@PVDF membrane.
[0046] Figure 4 It can be seen that the Ca3(PO4)2 / PSBMA@TA-APTES@PVDF membrane exhibits superhydrophilic properties.
[0047] Figure 5 It can be seen that the Ca3(PO4)2 / PSBMA@TA-APTES@PVDF membrane exhibits underwater superoleophobic properties.
[0048] Figure 6 It can be seen that the separation efficiency of Ca3(PO4)2 / PSBMA@TA-APTES@PVDF membrane for different types of oil-water emulsions can reach more than 99% with high flux. Specifically, the separation efficiency for cyclohexane is close to 40%, the separation efficiency for dichloroethane is 99%, the separation efficiency for toluene is about 90%, the separation efficiency for n-hexane is about 70%, and the separation efficiency for petroleum ether is about 52%.
[0049] Figure 7 It can be seen that the water circulation performance of Ca3(PO4)2 / PSBMA@TA-APTES@PVDF membrane is good.
[0050] Figure 8 It can be seen that the emulsion circulation performance of Ca3(PO4)2 / PSBMA@TA-APTES@PVDF membrane is good.
[0051] Embodiment 2:
[0052] Step 1: Pretreatment of PVDF base membrane: Wetting with a certain amount of ethanol.
[0053] Step 2: Preparation of TA-APTES@PVDF membrane:
[0054] TA (50 mg) was dissolved in 25 mL of deionized water, and then 700 μL of APTES was added, and the pretreated PVDF base membrane was placed in it. The membrane was shaken in a water bath at room temperature for 40 minutes to obtain a modified membrane with a rough surface modified by a micro-nanosphere coating.
[0055] Step 3: Preparation of PSBMA@TA-APTES@PVDF membrane:
[0056] 0.058 g FeCl3·6H2O, 0.01 g ammonium persulfate, 0.012 g N,N-methylenebisacrylamide and 0.1 g methacrylate sulfobetaine were dissolved in 6 mL deionized water, the membrane obtained in step (2) was placed in the solution, and the reaction was carried out under shaking in a water bath at room temperature for 2 h to obtain a zwitterionic hydrogel membrane.
[0057] Step 4: Preparation of Ca3(PO4)2 / PSBMA@TA-APTES@PVDF membrane:
[0058] Dissolve 100 mg of anhydrous CaCl2 in 20 mL of deionized water, and soak the membrane obtained in step (3) therein for 30 min; then soak it in water for 10 min; finally, transfer the membrane to the prepared 69.6 mg / 20 mL KH2PO4 solution and soak it for 30 min to obtain a Ca3(PO4)2 crystal-enhanced zwitterionic hydrogel membrane.
[0059] Embodiment 3:
[0060] Step 1: Pretreatment of PVDF base membrane: Wetting with a certain amount of ethanol.
[0061] Step 2: Preparation of TA-APTES@PVDF membrane:
[0062] TA (50 mg) was dissolved in 25 mL of deionized water, and then 700 μL of APTES was added, and the pretreated PVDF base membrane was placed in it. The membrane was shaken in a water bath at room temperature for 40 minutes to obtain a modified membrane with a rough surface modified by a micro-nanosphere coating.
[0063] Step 3: Preparation of PSBMA@TA-APTES@PVDF membrane:
[0064] 0.058 g FeCl3·6H2O, 0.01 g ammonium persulfate, 0.012 g N,N-methylenebisacrylamide and 0.2 g methacrylic acid sulfobetaine were dissolved in 6 mL deionized water, and the membrane obtained in step (2) was placed in the solution, and the reaction was carried out under shaking in a water bath at room temperature for 2 h to obtain a zwitterionic hydrogel membrane.
[0065] Step 4: Preparation of Ca3(PO4)2 / PSBMA@TA-APTES@PVDF membrane:
[0066] Dissolve 50 mg of anhydrous CaCl2 in 20 mL of deionized water, and soak the membrane obtained in step (3) therein for 30 min; then soak it in water for 10 min; finally, transfer the membrane to the prepared 69.6 mg / 20 mL KH2PO4 solution and soak it for 30 min to obtain a Ca3(PO4)2 crystal-enhanced zwitterionic hydrogel membrane.
[0067] Embodiment 4:
[0068] Step 1: Pretreatment of PVDF base membrane: Wetting with a certain amount of ethanol.
[0069] Step 2: Preparation of TA-APTES@PVDF membrane:
[0070] TA (50 mg) was dissolved in 25 mL of deionized water, and then 500 μL of APTES was added, and the pretreated PVDF base membrane was placed in it. The membrane was shaken in a water bath at room temperature for 40 minutes to obtain a modified membrane with a rough surface modified by a micro-nanosphere coating.
[0071] Step 3: Preparation of PSBMA@TA-APTES@PVDF membrane:
[0072] 0.058 g FeCl3·6H2O, 0.01 g ammonium persulfate, 0.012 g N,N-methylenebisacrylamide and 0.1 g methacrylate sulfobetaine were dissolved in 6 mL deionized water, the membrane obtained in step (2) was placed in the solution, and the reaction was carried out under shaking in a water bath at room temperature for 2 h to obtain a zwitterionic hydrogel membrane.
[0073] Step 4: Preparation of Ca3(PO4)2 / PSBMA@TA-APTES@PVDF membrane:
[0074] Dissolve 50 mg of anhydrous CaCl2 in 20 mL of deionized water, and soak the membrane obtained in step (3) therein for 30 min; then soak it in water for 10 min; finally, transfer the membrane to the prepared 69.6 mg / 20 mL KH2PO4 solution and soak it for 30 min to obtain a Ca3(PO4)2 crystal-enhanced zwitterionic hydrogel membrane.
[0075] Embodiment 5:
[0076] Step 1: Pretreatment of PVDF base membrane: Wetting with a certain amount of ethanol.
[0077] Step 2: Preparation of TA-APTES@PVDF membrane:
[0078] TA (50 mg) was dissolved in 25 mL of deionized water, and then 700 μL of APTES was added, and the pretreated PVDF base membrane was placed in it. The membrane was shaken in a water bath at room temperature for 40 minutes to obtain a modified membrane with a rough surface modified by a micro-nanosphere coating.
[0079] Step 3: Preparation of PSBMA@TA-APTES@PVDF membrane:
[0080] 0.058 g FeCl3·6H2O, 0.01 g ammonium persulfate, 0.012 g N,N-methylenebisacrylamide and 0.1 g methacrylate sulfobetaine were dissolved in 6 mL deionized water, the membrane obtained in step (2) was placed in the solution, and the reaction was carried out under shaking in a water bath at room temperature for 2 h to obtain a zwitterionic hydrogel membrane.
[0081] Step 4: Preparation of Ca3(PO4)2 / PSBMA@TA-APTES@PVDF membrane:
[0082] Dissolve 50 mg of anhydrous CaCl2 in 20 mL of deionized water, and soak the membrane obtained in step (3) therein for 30 min; then soak it in water for 10 min; finally, transfer the membrane to the prepared 80.0 mg / 20 mL KH2PO4 solution and soak it for 30 min to obtain a Ca3(PO4)2 crystal-enhanced zwitterionic hydrogel membrane.
[0083] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent transformation or modification made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a Ca3(PO4)2 crystal-enhanced zwitterionic hydrogel film, characterized in that: The PVDF separation membrane was used as the base membrane, the surface of the base membrane was hydrophilically modified by a micro-nanosphere coating prepared by TA-APTES and zwitterions, and then it was mineralized and modified by Ca3(PO4)2.
2. The method for preparing a Ca3(PO4)2 crystal-enhanced zwitterionic hydrogel film according to claim 1, characterized in that: The PVDF-based membrane used is a hydrophobic membrane.
3. The method for preparing a Ca3(PO4)2 crystal-enhanced zwitterionic hydrogel film according to claim 1, characterized in that: The membrane modified by the micro-nanosphere coating has a rough surface, and the raw material tannic acid used in the preparation process can be used as a catalyst for zwitterion free radical reaction in the next step.
4. The method for preparing a Ca3(PO4)2 crystal-enhanced zwitterionic hydrogel film according to claim 1, characterized in that: The prepared zwitterionic hydrogel membrane uses a polyphenol-metal dual autocatalytic method to initiate the polymerization of zwitterionic monomer methacrylic acid sulfobetaine at room temperature.
5. A method for preparing a Ca3(PO4)2 crystal-enhanced zwitterionic hydrogel film according to any one of claims 1 to 4, characterized in that: The steps include: Step 1: Pretreatment of PVDF base membrane: Wetting with ethanol; Step 2: Preparation of TA-APTES@PVDF membrane: TA was dissolved in deionized water, and then APTES was added, and the pretreated PVDF base membrane was placed in it, and the reaction was carried out in a water bath at room temperature to obtain a modified membrane with a rough surface modified by a micro-nanosphere coating; Step 3: Preparation of PSBMA@TA-APTES@PVDF membrane: Dissolve FeCl3·6H2O, ammonium persulfate, N,N-methylenebisacrylamide and methacrylate sulfobetaine in deionized water, put the membrane obtained in step 2 into the solution, and react in a water bath at room temperature to obtain a zwitterionic hydrogel membrane; Step 4: Preparation of Ca3(PO4)2 / PSBMA@TA-APTES@PVDF membrane: Dissolve approximately anhydrous CaCl2 in deionized water and soak the membrane obtained in step 3; Then soak it in water; finally, transfer the membrane to a KH2PO4 solution and soak it to obtain a zwitterionic hydrogel membrane enhanced by Ca3(PO4)2 crystals.
6. The method for preparing a Ca3(PO4)2 crystal-enhanced zwitterionic hydrogel membrane according to claim 5, characterized in that: Dissolve 40-60 mg of TA in 20-30 mL of deionized water, then add 500-1000 μL of APTES, put into the pretreated PVDF base membrane, and react in a water bath at room temperature for about 30 min to 1 h to obtain a modified membrane with a rough surface modified by a micro-nanosphere coating; Dissolve 0.058 g FeCl3·6H2O, 0.005-0.025 g ammonium persulfate, 0.01-0.02 g N,N-methylenebisacrylamide and 0.1-0.5 g methacrylate sulfobetaine in 5-10 mL deionized water; Shake the reaction in a water bath for about 1 to 3 hours; Dissolve 50-200 mg of anhydrous CaCl2 in 20 mL of deionized water, and soak the membrane obtained in step 3 for 10-30 min; then soak it in water for 5-10 min; finally, transfer the membrane to the prepared 60 mg / 20 mL-80 mg / 20 mL KH2PO4 solution and soak it for about 10-30 min.
7. A Ca3(PO4)2 crystal reinforced zwitterionic hydrogel membrane, characterized in that: The invention discloses a base membrane with a PVDF separation membrane, wherein the base membrane has a micro-nanosphere coating prepared by TA-APTES and Ca3(PO4)2 crystals.
8. The Ca3(PO4)2 crystal enhanced zwitterionic hydrogel membrane according to claim 7, characterized in that: The hydrogel film is prepared by the preparation method described in any one of claims 1 to 6.
9. Use of the Ca3(PO4)2 crystal reinforced zwitterionic hydrogel membrane of claim 7 or 8 for separation of oil-water emulsions.
Citation Information
Patent Citations
In-situ mineralized reinforced composite hydrogel and preparation method thereof
CN104177636A
Anti-pollution nanofiltration membrane based on tannic acid multi-layer assembly as well as preparation and application
CN111701463A
Preparation method and application of PAT / FS-50 heterogeneous composite membrane material
CN115155333A
Alg / M hydrogel composite membrane as well as preparation method and application thereof
CN116832625A
Preparation method of HNTs / PVDF (at) PDA / PSBMA composite membrane and application of HNTs / PVDF (at) PDA / PSBMA composite membrane in heavy metal oily wastewater separation
CN118698336A